Asthmatic Symptoms among Pupils in Relation to Winter Indoor and Outdoor Air Pollution in Schools in Taiyuan, China - Zhao, Zhuohui (National Institute of Environmental Health Sciences, 2008)
BACKGROUND: There are few studies on associations between children’s respiratory heath and air pollution in schools in China. The industrial development and increased traffic may affect the indoor exposure to air pollutants in school environment. Moreover, there is a need to study respiratory effects of environmental tobacco smoke (ETS) and emissions from new building materials in homes in China. OBJECTIVES: We studied the associations between pupils’ asthmatic symptoms and indoor and outdoor air pollution in schools, as well as selected home exposures, in a coal-burning city in north China. METHODS: A questionnaire survey was administered to pupils (11–15 years of age) in 10 schools in urban Taiyuan, collecting data on respiratory health and selected home environmental factors. Indoor and outdoor school air pollutants and climate factors were measured in winter. RESULTS: A total of 1,993 pupils (90.2%) participated; 1.8% had cumulative asthma, 8.4% wheezing, 29.8% had daytime attacks of breathlessness. The indoor average concentrations of sulfur dioxide, nitrogen dioxide, ozone, and formaldehyde by class were 264.8, 39.4, 10.1, and 2.3 μg/m(3), respectively. Outdoor levels were two to three times higher. Controlling for possible confounders, either wheeze or daytime or nocturnal attacks of breathlessness were positively associated with SO(2), NO(2), or formaldehyde. In addition, ETS and new furniture at home were risk factors for wheeze, daytime breathlessness, and respiratory infections. CONCLUSIONS: Indoor chemical air pollutants of mainly outdoor origin could be risk factors for pupils’ respiratory symptoms at school, and home exposure to ETS and chemical emissions from new furniture could affect pupils’ respiratory health.